COMPARISON OF SPERM ATTRIBUTES IN FROZEN THAWED SEMEN OF PURE AND CROSSBRED JERSEY BULLS - KUMAR, U; GAWANDE, A P; SAHATPURE, S K; PATI, P; RAJAK, S K (The Indian Journal of Animal Reproduction, 2016)
Thirty-six ejaculates (3 ejaculates / bull) of pure and crossbred Jersey bulls were used to compare sperm attributes of frozen thawed semen. The seminal attributes viz. semen volume, sperm concentration, post thaw motility and acrosome integrity were similar (p>0.05) between the breeds, whereas, the percentage of live sperm during post thaw period were higher (p<0.05) in pure compared to crossbred Jersey bulls. The overall sperm abnormalities as well as the majority of head, mid piece and tail abnormalities were similar (p>0.05) between pure and crossbred Jersey bulls, however, the proportion of detached / free head, bent mid piece, free tail and highly coiled tail was higher (p<0.05) in crossbred and the proportion of asymmetric head and terminally coiled tail was higher (p<0.05) in pure Jersey bull. In both breeds, the total sperm head abnormalities showed negative correlation with live sperm (p>0.05), HOST positive sperm (p>0.05) and acrosomal integrity (p<0.05). In brief, based upon the sperm attributes in frozen thawed semen, it can be concluded that semen quality of pure and crossbred Jersey bulls was almost similar.